(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Clinical learning environments (CLEs) are pivotal in shaping nursing competencies. In Pakistan, disparities in mentorship, infrastructure, and resource allocation across regions influence student perceptions significantly. Objective: This study compares nursing students’ perceptions of CLEs between urban (Karachi) and semi-urban/rural hospitals (Hyderabad, Khairpur, Larkana) and explores the factors underpinning these differences. Methods: A cross-sectional survey using the Clinical Learning Environment Inventory (CLEI) was administered to 120 BScN students. Both quantitative (independent t-tests, ANOVA via SPSS v26) and qualitative methods (thematic analysis) were employed. Results: Karachi students reported notably higher satisfaction regarding mentorship (mean = 3.5 vs. 2.9, p = 0.02), resource availability (3.8 vs. 2.6, p < 0.01), and peer collaboration (4.0 vs. 3.2, p = 0.03). Graphical representations reveal distinct clusters for urban and semi-urban responses. Qualitative findings highlighted themes such as the need for better supervision and reduced non-academic workload in semi-urban areas. Conclusion: Urban CLEs currently outperform semi-urban settings, largely due to superior infrastructure and structured mentorship. Policy reforms focusing on faculty training, resource allocation, and workload management are recommended to standardize educational outcomes across regions.